The American Thyroid Association risk stratification and long-term outcomes of differentiated thyroid cancer: a 20-year follow-up of patients in Saudi Arabia - Jammah, Anwar Ali; AlSadhan, Ibrahim Mohammed; Alyusuf, Ebtihal Y.; Alajmi, Mubarak; Alhamoudi, Abdullah; Al-Sofiani, Mohammed E. (Frontiers in Endocrinology, 2023)
Background: Studies have reported differing factors associated with poor outcomes in patients with differentiated thyroid cancer (DTC). We aimed to describe our 20 years' experience on the management of thyroid cancer TCDTC and identify predictors of treatment outcomes.We conducted a retrospective review of medical records of patients with DTC seen in the Thyroid Center (TC) at King Saud University Medical City (KSUMC) in Riyadh, Saudi Arabia between the years 2000 and 2020. Demographic and clinical data includingThe tumor size, lymphovascular invasion, and obesity are strong predictors of a worse response to therapy among patients with DTC. Patients with obesity should be carefully followed up regardless of their risk stratification in light of the recent compelling evidence associating obesity to thyroid cancer and its higher risk of a worse disease outcome.ATA risk stratification is well correlated with patient long-term outcomes.